(untitled) (University of Thi-Qar Journal for Engineering Sciences, 2022)
This paper investigates a comparison of wear behavior under laser surface hardening for two different kinds of aluminum alloys. Experimental investigations of wear processing were carried out under different load conditions 5, 10,15,20,25 N and with constant sliding speed 2.199 m/s for 15 min. Also changing sliding velocities 1.319, 2.199, 3.078, 3.958 m/s with constant load 20 N for 15 min. Wear machine operate with constant disc rotating at 750 r.p.m. Trails of laser hardening were performed by using pulse Nd:YAG laser with three level energies 500 , 750 , 1000 mJ. Different wear tests were made such as, measurement of depth of hardening, micro-hardness and microstructure examination. This work is shown that the highest amount of laser energy is affected on increasing the micro hardness of 2024 alloy, while it has little or no effect of laser treatment for 7075 alloy. Also wear rates were significantly decreased for 2024 alloy more than 7075 alloy. Photomicrographs show that refining of grains after laser treatment for 2024 alloy more than 7075 alloy.